Spred2 Regulates High Fat Diet-Induced Adipose Tissue Inflammation, and Metabolic Abnormalities in Mice - Ohkura, Takahiro; Yoshimura, Teizo; Fujisawa, Masayoshi; Ohara, Toshiaki; Marutani, Rie; Usami, Kaya; Matsukawa, Akihiro (Frontiers in Immunology, 2019)
Chronic low-grade inflammation in visceral adipose tissues triggers the development of obesity-related insulin resistance, leading to the metabolic syndrome, a serious health condition with higher risk of cardiovascular disease, diabetes, and stroke. In the present study, we investigated whether Sprouty-related EVH1-domain-containing protein 2 (Spred2), a negative regulator of the Ras/Raf/ERK/MAPK pathway, plays a role in the development of high fat diet (HFD)-induced obesity, adipose tissue inflammation, metabolic abnormalities, and insulin resistance. Spred2 knockout (KO) mice, fed with HFD, exhibited an augmented body weight gain, which was associated with enhanced adipocyte hypertrophy in mesenteric white adipose tissue (mWAT) and deteriorated dyslipidemia, compared with wild-type (WT) controls. The number of infiltrating macrophages with a M1 phenotype, and the crown-like structures, composed of macrophages surrounding dead or dying adipocytes, were more abundant in Spred2 KO-mWAT compared to in WT-mWAT. Exacerbated adipose tissue inflammation in Spred2 KO mice led to aggravated insulin resistance and fatty liver disease. To analyze the mechanism(s) that caused adipose tissue inflammation, cytokine response in mWAT was investigated. Stromal vascular fraction that contained macrophages from Spred2 KO-mWAT showed elevated levels of tumor necrosis factor α (TNFα) and monocyte chemoattractant protein-1 (MCP-1/CCL2) compared with those from WT-mWAT. Upon stimulation with palmitate acid (PA), bone marrow-derived macrophages (BMDMs) derived from Spred2 KO mice secreted higher levels of TNFα and MCP-1 than those from WT mice with enhanced ERK activation. U0126, a MEK inhibitor, reduced the PA-induced cytokine response. Taken together, these results suggested that Spred2, in macrophages, negatively regulates high fat diet-induced obesity, adipose tissue inflammation, metabolic abnormalities, and insulin resistance by inhibiting the ERK/MAPK pathway. Thus, Spred2 represents a potential therapeutic tool for the prevention of insulin resistance and resultant metabolic syndrome.